Monitoring Spike Potential and Abrupt Impedance Rise with Concomitant Temperature/Contact Force Change for Timely Detection of the Occurrence of “Silent” or “Nonaudible” Steam Pop - Chengye Di; Qun Wang; Yanxi Wu; Longyu Li; Wenhua Lin (Journal of Interventional Cardiology)
Aim. Steam pop (SP) during radiofrequency catheter ablation (RFCA) for pulmonary vein isolation (PVI) may cause cardiac perforation, which may require drainage and emergent thoracotomy or even lead to death. Data investigating the timely detection of the occurrence of “silent” or “nonaudible” SP events are limited. Methods and Results. A total of 516 consecutive atrial fibrillation (AF) patients who underwent index PVI were included in this retrospective observational study. The duration, power, impedance, temperature, and contact force (CF) of RFCA were continually monitored and recorded throughout the procedure. A total of 15 (2.9%) audible SP events occurred in 14 patients; 2 of the patients developed pericardial tamponade, 1 patient underwent drainage, and 1 patient underwent emergent thoracotomy. The time from RFCA initiation to the occurrence of audible SP was 19.4 ± 6.9 s. Abrupt temperature change occurred in 13 (86.7%) of the 15 SP events, of which 8 (53.3%) exhibited an abrupt temperature rise of 2.3 ± 1.0°C, 5 (33.3%) exhibited an abrupt temperature drop of 2.3 ± 1.3°C, and 2 (13.3%) exhibited no discernible temperature change. Conclusions. In conclusion, simultaneously recorded spike potentials and abrupt impedance rise with concomitant temperature and/or CF change could be a feasible method for the timely detection of the occurrence of audible, “silent,” or “nonaudible” SP events, particularly in regions where the risk of perforation may be of concern.